Estimating exercise intensity for freestyle ski mogul - Nakazato, K.; Hakamada, N.; Ishige, Y. (Journal of High Performance Sport, 2019)
The purposes of this study were to estimate exercise intensity during mogul skiing using heart rate and to clarify the physiological characteristics of mogul skiing using blood lactate concentration. Additionally, to clarify the characteristics of mogul skiing by comparison, a 40-s incline side jump test and mogul ski performance points were compared. Six male and six female subjects belonging to the Japanese national ski team took part in this study. The study took place at the moguls World Cup in Tazawako, Akita, Japan. Blood lactate concentrations were measured three, five, and seven minutes after the finish using a lactate auto analyzer. Additionally, relative blood lactate concentration was calculated with respect to the maximum blood lactate concentration, which was measured after the 40-s incline side jump test. Three male and three female participants took part in the heart rate measurement during the competition. To estimate exercise intensity, relative heart rate during the competition was calculated with respect to the maximum heart rate measured during the maximum oxygen uptake test. To evaluate the relationships between lactate concentration and time point and between the number of 40-s incline side jumps, lactate concentration after the 40-s incline side jump test and time point, Pearson's correlation coeffcient was tested. The average maximum blood lactate concentration after the competition was 7.6mmol·L-1 for the males and 8.6mmol·L-1 for the females. The average heart rate during the competition was 182.3bpm for the males and 182.8bpm for the females. There was no correlation between lactate concentration and time point; however, there was a positive correlation between the number of 40-s incline side jumps and time point. Based on the results of this study, mogul skiing can be defned as a high-intensity exercise requiring anaerobic endurance.